Analisis Determinan Capital Buffer pada Bank Umum Syariah di Indonesia Periode 2015-2020 - Dwi Eva Kurnianingsih; Dadang Hermawan; Ine Mayasari (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The purpose of this study was to determine the effect of Non Performing Financing (NPF), Return On Equity (ROE), Loans To Total Assets (LOTA), and Economic Growth on Capital Buffer. This study uses a sample of 12 Islamic Commercial Banks in the Financial Services Authority (OJK) for the 2015-2020 period using the purposive sampling method. The research data is taken from secondary data in the form of financial reports and economic growth reports. The analytical method used to solve the problem in this research is panel data regression analysis. The results showed that partially the variables NPF, ROE and LOTA had a negative and significant effect on the Capital Buffer. Economic growth has no significant effect on the Capital Buffer. Simultaneously the variables of NPF, ROE, LOTA, and economic growth have a role in explaining the Capital Buffer of Islamic commercial banks in Indonesia.